The Relationship between Family Ownership, CEO Demographic Characteristics and Dividend Policy: Evidence from Indonesia - Muhammad Madyan, - (Korea Distribution Science Association (KODISA), 2021)
The objective of this study is to examine the effect of family ownership and family CEO on the dividend policy of family firms by using the demographic characteristics of the CEO as a moderator. Dividend policy is a decision taken by the firm in determining whether the profits earned by the firm will be distributed to shareholders in the form of dividends or will be reinvested in the company as retained earnings for future internal resources. Using samples from non-financial family firms listed on the Indonesian Stock Exchange in 2013-2017, 93 firms were selected based on adequate data. We also used logit regressions to provide robustness. The results show that family ownership and family CEO have a positive effect on the dividend payout ratio. This finding supports the family income hypothesis. Among CEO demographic characters, CEO age significantly strengthens the positive effect of family CEO on dividend payout ratio. While CEO tenure does not significantly strengthen the positive effect of family CEOs on dividend payout ratios. Meanwhile, leverage, ROA, and firm size significantly affect the dividend payout ratio, but firm age does not significantly affect the dividend payout ratio.